Nanomedicine in Psychiatry: New Therapeutic Opportunities from Research on Small RNAs. Issue 8 (16th September 2016) - Milanesi, Elena; Maj, Carlo; Bocchio‐Chiavetto, Luisella; Maffioletti, Elisabetta
ABSTRACT: Preclinical Research Alterations in small non‐coding RNAs have been observed in many human disease states including cancer, cardiovascular, developmental, neurological, and psychiatric disorders. These molecules have recently raised the interest of the scientific community for novel therapeutic approaches. Nanotechnologies, including the development of sophisticated nanoparticles, offer new ways for the delivery of small RNA‐based therapies. The nanoparticle delivery method appears attractive, but so far most of the work in this area has been conducted in the context of cancer. New therapeutic strategies are needed for psychiatric disorders, where treatment is often ineffective, leading to frequent patient hospitalizations and a growing economic burden. In this article, we discuss the role of small RNAs in psychiatric diseases and how this new knowledge, combined with innovations in nanotechnologies, could lead to the development of novel therapeutic approaches. Drug Dev Res 77 : 453–457, 2016. © 2016 Wiley Periodicals, Inc.